P-Adic Riesz Potential and Its Commutators on Morrey-Herz Spaces. (16th May 2022) - Shi, Yanlong; Shi, Yafeng; Chen, Shenbao
Abstract : In this paper, we establish the boundedness of p -adic Riesz potential on Morrey-Herz spaces, as well as the λ -central BMO estimates for multilinear commutators of p -adic Riesz potential on Morrey-Herz spaces.